Age Differences among Female Sex Workers in the Philippines: Sexual Risk Negotiations and Perceived Manager Advice - Lianne A. Urada; Robert M. Malow; Nina C. Santos; Donald E. Morisky (AIDS Research and Treatment, 2012)
Consistent condom use among high risk groups such as female sex workers (FSWs) remains low. Adolescent female sex workers are especially at higher risk for HIV/STI infections. However, few published studies have compared the sexual risk negotiations among adolescent, emerging adult, and older age groups or the extent a manager’s advice about condom use is associated with an FSW’s age. Of 1,388 female bar/spa workers surveyed in the southern Philippines, 791 FSW who traded sex in the past 6 months were included in multivariable logistic regression models. The oldest FSWs (aged 36–48) compared to adolescent FSWs (aged 14–17) were 3.3 times more likely to negotiate condoms when clients refused condom use. However, adolescent FSWs received more advice from their managers to convince clients to use condoms or else to refuse sex, compared to older FSWs. Both adolescent and the oldest FSWs had elevated sexually transmitted infections (STIs) and inconsistent condom use compared to other groups. Having a condom rule at the establishment was positively associated with condom negotiation. Factors such as age, the advice managers give to their workers, and the influence of a condom use rule at the establishment need to be considered when delivering HIV/STI prevention interventions.